Behavior Analysis and Cinema: Assessment of the evidences supporting the Kuleshov Effect and an interpretation of its behavioral processes: Uma Interpretação Analítico-Comportamental do Efeito Kuleshov - Anschau de Biassio, Victor; Dittrich, Alexandre (Perspectivas em Análise do Comportamento, 2019)
The Kuleshov Effect is an often quoted and influent process in the cinematographic business. As it is usually described, it consists in the alteration of the perception of a stimulating situation, evaluated by a report emitted by observers of a photogram sequence. The present article has the objective of answering two questions: (1) Which empirical evidences support the existence of the Kuleshov Effect?; and (2) How this process can be understood from the perspective of the behavior analysis? The material of analysis was collected from a wide review of literature, contemplating books specialized in cinema history, electronic pages of renowned film schools and databases relevant to Psychology. After the analysis of the collected material, we concluded that: (1) The available evidences about the methodological details and the very occurrence of Kuleshov’s experiments are scarce; and (2) The processes potentially involved in the Kuleshov Effect can be understood with the help of respondent and operant variables, emphasizing the relevance of the social-verbal contingences and of the history of individual interaction with the cinematographic arts. We suggest the importance of opening or amplifying the channels of collaboration between Behavior Analysis, the cinematographic theory and the arts in general.